Prevention of head louse infestation: a randomised, double-blind, cross-over study of a novel concept product, 1% 1, 2-octanediol spray versus placebo. Issue 5 (30th May 2014) - Burgess, Ian F; Brunton, Elizabeth R; French, Rebecca; Burgess, Nazma A
Abstract : Objectives: To determine whether regular use of a spray containing 1, 2-octanediol 1%, which has been shown to inhibit survival of head lice, is able to work as a preventive against establishment of new infestations. Setting: Randomised, double-blind, cross-over, community study in Cambridgeshire, UK. Participants: 63 male and female schoolchildren aged 4–16 years judged to have a high risk of recurrent infestation. Only the youngest member of a household attending school participated. Interventions: Participants were treated to eliminate lice, randomised between 1% octanediol or placebo sprays for 6 weeks then crossed-over to the other spray for 6 weeks. Parents applied the sprays at least twice weekly or more frequently if the hair was washed. Investigators monitored weekly for infestation and replenished supplies of spray. Primary and secondary outcome measures: The primary endpoint was the time taken until the first infestation event occurred. The secondary measure was safety of the product in regular use. Results: Intention-to-treat analysis found a total of 32 confirmed infestations in 20 participants, with 9 of them infested while using both products. In these nine participants the time to first infestation showed a significant advantage to 1% octanediol (p=0.0129). Per-protocol analysis showed only trends because the population included was not large enough to demonstrate significance. There were no serious adverse events and only two adverse events possibly related to treatment, one was a case of transient erythema and another of a rash that resolved after 5 days. Conclusions: Routine use of 1% octanediol spray provided a significant level of protection from infestation. It was concluded that this product is effective if applied regularly and thoroughly. Trial registration number: ISRCTN09524995.